Draft report on hospital administration from the point of view of the patient : to be presented at the National Conference of Labour Women at Blackpool
1931-06 1931 1930s 5 pages - 3- in the paying wards and even paying patients side by side with non-paying may be more zealously considered than those in the other wards. E. Representation of Working Women. There is a great need of working class representatives, and especially women, on the management of hospitals. This can be more easily met when they are under Public Health Authorities but owing to the small number of working women on the Councils is still far short of the need. It is often not realised that under the 1929 Act it is possible to co-opt women on to the governing bodies of municipal hospitals. On voluntary hospitals there are very rarely such representatives and their need in supervising arrangements suitable to the patients is greatly felt. 2. NEEDS OF IN-PATIENTS. A. Waking hour for patients. Dr.Somerville Hastings memorandum. B. Ward Furniture. Memorandum. C. Food. Whilst it is realised that the actual diet of a patient must be decided by those in charge of the case, yet there is much room for improvement in general details concerning hospital food. The system prevalent in many hospitals of patients supplying part of it such as butter, tea and eggs should be abolished and the hospital should be responsible for providing all the food needed by the patients. This would dispense with the practice of keeping food in lockers, though an exception might be allowed for fruit and sweets or food that can be kept in a tin such as biscuits. Attention should be given to the necessity of serving hot food hot and not warm. This is not a difficult matter, requiring only suitable equipment to meet the relative positions of wards and kitchen. Of late years the large hospitals have paid more attention to having trained women in the kitchen but many of the smaller hospitals have not yet a trained kitchen superintendent. D. Noise. Hospitals should not face on to noisy and crowded thoroughfares. Those which now do so should be replaced as soon as possible by buildings on more suitable sites. The strain of continuous noise is a heavy one and in a hospital so placed, care should be taken to give the quieter wards to those cases needing them most, and not, as is done now, to reserve these for paying patients. Another misery for patients is the presence in a large ward of some patient who is troublesome because of his or her illness to others. For these there should be some small side wards to utilise at need. 292/842/1/8